Receiver function structure beneath four seismic stations in the Sumatra region - Hidayat, Dannie. (2013)
We estimated the velocity structure beneath four three-component broad-band seismic stations in the Sumatra region by the joint inversion of teleseismic receiver functions and surface wave group velocities. The stations, part of GEOFON network GE, are located in diverse geologic settings including backarc basins, forearc basins, and the forearc ridge. The stations are distributed roughly trench-parallel, providing samples of conditions along the length of Sumatra. 143 receiver functions were computed by employing an iterative, time-domain deconvolution in order to minimize acausal noise. The teleseismic observations at each station were grouped by back azimuth and ray parameter and then stacked to increase the signal to noise ratios. Surface wave group velocity dispersion was measured for paths across the Sunda block from events to the northeast of the stations. P-wave velocity profiles were derived by inverting the stacks and group velocity data using a linearized time-domain inversion scheme with an interpolated CRUST2.0 global model for input. The results differ significantly from CRUST2.0, and reflect the diversity of geologic environments within which the stations are located. Crustal thicknesses beneath the stations range from 16.0 km at the forearc to 30.0 km at a backarc basin. These results add to the available velocity and crustal thickness data for the Sumatra region.